PSVIII-30 Reduced-lignin alfalfa digestibility and effects on performance of growing beef steers. (30th November 2020) - Karls, Caleb; Undersander, Dan; Combs, David; Donnelly, Derek; Engel, Cara; Miller, Donald; Schaefer, Dan
Abstract: Novel alfalfa varieties have been developed to have less lignin by genetic modification, (HarvXtra, Forage Genetics International) and by conventional breeding, (HiGest 360, Alforex Seeds). Second crop (d 29) of these alfalfas and a control, LegenDairy XHD (Winfield Solutions LLC), were harvested as high moisture wrapped bales (45.9–51.6 % DM) at the Arlington Agricultural Research Station (AARS) located near Arlington, WI, on July 5, 2017. The objectives of these experiments were to characterize novel reduced-lignin alfalfa varieties, assess their effects on growth of beef steers, and determine digestibilities using a total fecal collection trial. Treatments were fed ad libitum as alfalfa baleage to 300 kg (initial weight) black-hided beef steers, (n = 72, 4 pens/treatment, 83 d). Steers were fed solely alfalfa baleage and offered a trace mineral salt block by way of fence line feed bunks. Alfalfa lignin values were 7.56, 7.18, and 6.3% DM (P = 0.34) for LegenDairy, HiGest and HarvXtra, respectively. Steers gained 0.94, 1.00, and 1.07 kg hd -1 d -1 (P = 0.25) for LegenDairy, HiGest and HarvXtra, respectively. The same harvested alfalfa was used in a total collection fecal trial with fecal collection bags (Table 1). Numerical differences between alfalfa digestibilities were observed but no significant treatment effects were detected. Total tract NDF digestibilities (TTNDFD) for harvested alfalfas were 33.9, 35.0 and 40.3 % NDF (P = 0.079) for LegenDairy, HiGest and HarvXtra, respectively. Alfalfa lignin concentration differences were not detected through acid detergent-lignin analysis of harvested bales. While the ranking of lignin concentrations, digestibilities, and growth rates followed prevailing logic, alfalfa variety treatment effects were not detected. Experimental designs with greater sensitivity should be implemented in the future.